Futility risk model for predicting outcome after cardiac resynchronization therapy defibrillator implantation: data from a nationwide analysis. (24th May 2021) - Maille, B; Bodin, A; Bisson, A; Herbert, J; Franceschi, F; Koutbi-Franceschi, L; Hourdain, J; Martinez, E; Zabern, M; Deharo, J-C; Fauchier, L
Abstract: Funding Acknowledgements: Type of funding sources: None. Objective. Risk-benefit assessment for cardiac resynchronization therapy defibrillator (CRT-D) over a CRT pacemaker (CRT-P) is still a matter of debate. We aimed to identify patients with a bad outcome within one year after CRT-D implantation, and to develop a Futile CRT-D score. Methods. Based on the administrative hospital-discharge database, all consecutive patients treated with CRT-D implantation in France between 2010 and 2019 were included. A prediction model was derived and validated for one-year all-cause death after CRT-D implantation (considered as futility) by using split-sample validation. Results. 28, 503 patients were included in the analysis (mean age 68 ± 10 years); 2, 139 (7.5%) deaths were recorded in the first year. In the derivation cohort (n = 14, 252), the final logistic regression model included as main predictors of futility older age, diabetes, mitral regurgitation, history of hospital stay with heart failure, history of pulmonary oedema, atrial fibrillation, renal, pulmonary, liver, or thyroid disease, denutrition and anemia. Based on Futile CRT-D score, 17% of these patients were categorized at high risk (Futile CRT-D score ≥13) and predicted futility at 17%. Conclusion.   The futility CRT-D score, established from a large nationwide cohort of patients treated with CRT-D may provide a relevant tool for optimizing healthcare decision.